2010
DOI: 10.1177/8755123310378454
|View full text |Cite
|
Sign up to set email alerts
|

How Can Elementary Teachers Measure Singing Voice Achievement? A Critical Review of Assessments, 1994-2009

Abstract: The first content standard of the National Standards for Music Education requires that students sing, alone and with others, a varied repertoire of music. Although state and district elementary music curricula vary widely, many are based on the National Standards for Music Education and therefore include singing as a primary content area and method of teaching and learning music. However, classroom assessments of singing voice achievement and development vary widely, and information about reliability and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…As test design becomes better understood, music teachers can more confidently implement formal assessments of singing than may currently occur in classrooms (Salvador, 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As test design becomes better understood, music teachers can more confidently implement formal assessments of singing than may currently occur in classrooms (Salvador, 2010).…”
mentioning
confidence: 99%
“…Researchers in music education have created unique measures of singing (Salvador, 2010) and have tested many different samples across the elementary grades in order to describe properties like singing range, accuracy, and other features (Hedden, 2012). Children have demonstrated widely varying competencies, from 9-38% of children deemed "inaccurate" (Goetze & Cooper, 1990) to 75-90% in one sample defined as "non-singers" (Levinowitz et al, 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reviews suggested that there was a need for alignment among studies regarding terminology (Welch, 1979a) and methods of measurement (Goetze et al, 1990). The need is reflected again in subsequent literature reviews devoted to the assessment of singing ability (Salvador, 2010;Welch, 1994).…”
Section: The Handbook Of Research On Music Teaching and Learning (199mentioning
confidence: 99%